Strategi Pengembangan Pariwisata Desa dalam Meningkatkan Pendapatan Asli Desa di Desa Pengkelak Mas Kecamatan sakra Barat: Village Tourism Development Strategy to Increase Village Original Income in Pengkelak Mas Village, West Sakra District - Lalu Muhammad Abdul Azis (Lembaga Pendidikan Al-Gafari, 2026)
Villages, as the smallest units of government, possess significant potential in the tourism sector, particularly those with unique cultural characteristics, natural beauty, and local wisdom. This study aims to analyze village tourism development strategies in increasing Village Original Revenue (Village-Owned Revenue). The research employs a qualitative approach, with data collected through interviews, observations, and documentation. The results indicate that village tourism development can be implemented through several key strategies, including the development of local tourism potential, community empowerment, the development of supporting infrastructure, as well as promotion and collaboration with external stakeholders. These strategies have proven effective in increasing tourist visits and making a significant contribution to the growth of Village Original Revenue. However, village tourism development also faces several challenges, such as limited funding, inadequate human resource capacity, and environmental sustainability issues. Therefore, sustainable and collaborative planning is required to ensure that village tourism development can be carried out optimally and sustainably.